2012
DOI: 10.1021/la203972k
|View full text |Cite
|
Sign up to set email alerts
|

In Situ ATR-FTIR Studies on MgCl2-Diisobutyl Phthalate Interactions in Thin Film Ziegler–Natta Catalysts

Abstract: To study the surface structure of MgCl(2) support and its interaction with other active components in Ziegler-Natta catalyst, such as electron donors, we prepared a thin film analogue for Ziegler-Natta ethylene polymerization catalyst support by spin-coating a solution of MgCl(2) in ethanol, optionally containing a diester internal donor (diisobutyl-ortho-phthalate, DIBP) on a flat Si crystal surface. The donor content of these films was quantified by applying attenuated total internal reflection-Fourier trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 86 publications
3
42
0
Order By: Relevance
“…The function of the cocatalyst is well known to act as activator to reduce and alkylate the transition metal generating a Ti-C bond, which is responsible for the generation of active sites and essential for monomer insertion. [30][31][32] Alkyl aluminum can also scavenge impurities in the polymerization system. But too large amount of cocatalyst may lead to deactivation of the active sites through over-reduction of the active transition metal and also enhanced the chain transfer reaction to cocatalyst, which was not benefi cial for increasing the catalyst activity.…”
Section: Ethylene Homopolymerization and Characterization Of The Polymentioning
confidence: 99%
“…The function of the cocatalyst is well known to act as activator to reduce and alkylate the transition metal generating a Ti-C bond, which is responsible for the generation of active sites and essential for monomer insertion. [30][31][32] Alkyl aluminum can also scavenge impurities in the polymerization system. But too large amount of cocatalyst may lead to deactivation of the active sites through over-reduction of the active transition metal and also enhanced the chain transfer reaction to cocatalyst, which was not benefi cial for increasing the catalyst activity.…”
Section: Ethylene Homopolymerization and Characterization Of The Polymentioning
confidence: 99%
“…Of note, Ziegler–Natta catalysts, which are composed of titanium active sites supported on magnesium chloride, produce a significant fraction of the world's polyethylene . Due to the acute sensitivity of the MgCl 2 to both ambient conditions and electron irradiation, electron microscopy has not fully characterized the pristine atomic and defect structure of Ziegler–Natta catalyst supports . Moreover, previous works have paid little respect to the impact of electron dose on the observed atomic structure of MgCl 2 , despite the fact that the beam‐sensitivity of MgCl 2 has been known.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that in the absence of donors the sintering of MgCl 2 leads to very large MgCl 2 platelets that offer only a very small number of coordination sites whereas in the presence of donors the MgCl 2 crystallites remain much smaller because of the stabilization of the surface sites by donor adsorption. 36 However, all of these studies offered a static picture of the most likely situation with and without donors, but it did not give insight into the dynamics of these processes. In other words, they provided no clue as to the dynamics of MgCl 2 reconstruction or the capability of the donors to move on the MgCl 2 surfaces and to induce MgCl 2 reconstruction or the capability of the donors to move on the MgCl 2 surfaces even during polymerization.…”
Section: ■ Introductionmentioning
confidence: 99%